2006
DOI: 10.1111/j.1471-1842.2006.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing efficient search strategies to identify reports of adverse effects in medline and embase

Abstract: Objective: This study aimed to assess the performance, in terms of sensitivity and precision, of different approaches to searching  and  to identify studies of adverse effects. Methods: Five approaches to searching for adverse effects evidence were identified: approach 1, using specified adverse effects; approach 2, using subheadings/qualifiers; approach 3, using text words; approach 4, using indexing terms; approach 5, searching for specific study designs. The sensitivity and precision of these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
3
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 32 publications
2
100
3
4
Order By: Relevance
“…For reviews that search for all adverse effects on a given intervention, a search using floating subheadings (such as ''adverse effects,'' or ''complications'') is recommended [4,7,29]. In this study, only one review reported using floating subheadings for adverse effects.…”
Section: Search Terms For ''Outcomes'' (Adverse Effects)mentioning
confidence: 97%
See 2 more Smart Citations
“…For reviews that search for all adverse effects on a given intervention, a search using floating subheadings (such as ''adverse effects,'' or ''complications'') is recommended [4,7,29]. In this study, only one review reported using floating subheadings for adverse effects.…”
Section: Search Terms For ''Outcomes'' (Adverse Effects)mentioning
confidence: 97%
“…Free access to particular sources (such as MEDLINE) may influence some of the decisions on which sources to search. Yet studies have indicated that MEDLINE is not the most useful source of adverse drug effects information [7,27,28]. The absence of more detailed research may also prevent researchers from selecting an optimal core set of databases.…”
Section: Few Databases Searchedmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies stress the importance of the correct use of MeSH in comparison with free text when recovering scientific literature (Golder et al, 2006;Chang et al, 2006). The suitability of search equations (themed filters or documentary languages) is highlighted by using Descriptors to recover specific articles or a specific type of document with a high degree of sensitivity (Haynes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that whilst Medline is recommended here due to its availability, EMBASE and the Science Citation Index (SCI) might produce higher yields of adverse effects evidence [20]. A search filter for adverse effects has been developed and validated [21]. The filter focusses on drug adverse events and a different approach might be required for non-drug interventions [22].…”
Section: Treatment Effectsmentioning
confidence: 99%